Aliran Aliran dalam Pendidikan - Wafiq Zahira Mardatilah; Rivo Kurnia Ilahi; Rahmi Putri (Pusat Riset dan Inovasi Nasional, 2025)
Education as a systematic effort to form a complete human being has given birth to various schools of thought that have developed throughout history. Each school has unique characteristics in understanding the nature of education, goals, methods and roles of educators and students. The traditionalist school of education emphasizes the importance of inheriting past values ​​and knowledge through structured methods. Meanwhile, progressivism prioritizes students' learning experiences with a flexible and contextual approach. Existentialism focuses on individual freedom in determining the direction of education, while essentialism focuses on mastering basic knowledge and core skills. The flow of social reconstructionism encourages education as a tool to improve social conditions and create better social change. This research aims to provide a comprehensive overview of the basic concepts of various schools of education, so that it can become a theoretical basis for developing educational models that are relevant to today's challenges.